Rediscovery of the Ordinary! – On the Omnipresence and Aesthetic of Popular Culture (KULT_online, 2012)
Das Recht der Gewöhnlichkeit. Über populäre Kultur (The Right of Ordinariness: On Popular Culture) – a collection of cultural essays by Kasper Maase – is to be seen as an invitation to reinterpret and (de)contextualize processes of cultural adoption, allocation, differentiation, and distinction in post-war German society. The main topics are marked by questions about the Americanization of German popular culture, about the aestheticizing of everyday life, by questions about the system of reference and about the shaping and homogenizing moments of popular culture. These themes are discussed along an actor-focused analysis of youth and entertainment culture as well as along historical, illustrative examples of western German common culture and their westernization. Instead of being a complex history of popular culture, a methodological guide, or hierarchically structured theoretical reflections, Maase's essays offer a fascinating analytical inspiration on the way to discover popular culture and its sights in our everyday experience.